The legal nature of Jordanian Public Security Agency’s activities - Alzyoud, Nayef Mohammed Hussien (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at identifying the legal nature of the activities of the employees of the Public Security Agency, as it is one of the official state departments in spreading security and maintaining public order, and reviewing the role of the public security personnel in administrative control, judicial seizure, preliminary investigation, dealing with juvenile cases, and investigation of new crimes such as human trafficking and electronic crimes.To achieve the objectives of the study, the descriptive analytical approach was used in addition to the legal method, as they are among the most appropriate scientific research methods for the purposes of this study.The study revealed a number of results, including that the Public Security Agency is an armed statutory body that the state bears the responsibility for establishing, organizing, spending on it and providing it with what is necessary to carry out its duties of maintaining security and order. To achieve this, the Public Security Agency follows a comprehensive security strategy whose dimensions are the preventive dimension, the social dimension, the human dimension, the ethical dimension, and the civilization dimension to achieve a set of goals. The study also revealed that one of the most important duties entrusted to the Jordanian public security personnel is consistent with the axes of the public security strategy, including the duties of the main force, administrative control, judicial control, and the original powers of public security personnel for the initial investigation, dealing with juvenile delinquent cases, and the initial investigation of crimes. New developments, such as human trafficking crimes, combating electronic crimes, and protecting intellectual property.In light of the results, a set of recommendations were set, including an emphasis on spreading legal awareness among public security personnel with regard to disciplinary responsibility, criminal responsibility, civil liability, the responsibility of the administrative apparatus entrusted to them during the performance of their duty, and the need to spread awareness among citizens and policemen as far as possible. Whether the role of the Public Security Agency is not limited to security performance, but also to provide service to citizens and society, and then the public interest requires concerted efforts from both parties together to achieve this interest.
Keywords: Jordanian public security apparatus; administrative control; judicial control; preliminary investigation